2006
DOI: 10.2165/00007256-200636030-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet and Exercise for the Maintenance of Fat-Free Mass and Resting Metabolic Rate During Weight Loss

Abstract: The incidence of obesity is increasing rapidly. Research efforts for effective treatment strategies still focus on diet and exercise programmes, the individual components of which have been investigated in intervention trials in order to determine the most effective recommendations for sustained changes in bodyweight. The foremost objective of a weight-loss trial has to be the reduction in body fat leading to a decrease in risk factors for metabolic syndrome. However, a concomitant decline in lean tissue can f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
254
3
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(284 citation statements)
references
References 134 publications
13
254
3
14
Order By: Relevance
“…[31][32][33] Muscle strength, decreases in visceral adiposity, and improved insulin sensitivity have all been associated with higher levels of physical activity. 34,35 Future studies should investigate diabetes risk, exercise, lean muscle mass, and visceral adiposity in healthy weight individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Muscle strength, decreases in visceral adiposity, and improved insulin sensitivity have all been associated with higher levels of physical activity. 34,35 Future studies should investigate diabetes risk, exercise, lean muscle mass, and visceral adiposity in healthy weight individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A high fat content in the diet increases weight gain and the risk of developing symptoms of the 'metabolic syndrome' in a number of species, including human beings 2,24 and various rodents. [3][4][5][6] This study investigated whether and how such an effect may be influenced by physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The need to implement studies on high-protein diets and physical activity has been stressed recently (15) . The effects of a 7 d high-protein diet on endurance performance have been investigated by Jarvis et al (6) and Macdermid & Stannard (7) , who reported ergolytic effects on cycling endurance performance in recreational and highly trained athletes, respectively.…”
Section: Discussionmentioning
confidence: 99%